(3CSGSjGJ GSJNOGe fhGaP eGjcQhShaJ eY GYJeGO GddZI GdYQHjI (B:s (3HGYJeGO GddZI GdYQHjI (BMicrosoft windows /s - (3MSjf MSf MSjf HQcGJs ((3GdbGgQI (B:s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY,s, 1994)
(3eG gi GdfhGaP(B.s
Keywords: (3eGjcQhShaJ hjfOhR (B((3eda MGShH(B)s; (3fXe GdJTZjd (B((3MGSHGJ EdcJQhfjI(B)s